Managing strategic surprise : lessons from risk management and risk assessment - Bracken, Paul J.; Bremmer, Ian, 1969-; Gordon, David, 1950- (Cambridge University Press, 2008)
Asks whether risk management techniques can be successfully applied to contemporary national security challenges.